2022
DOI: 10.1002/jsid.1116
|View full text |Cite
|
Sign up to set email alerts
|

Visual search during dynamic displays: Effects of velocity and motion direction

Abstract: The visual search performance during dynamic environment has been demonstrated that could be affected by the motion of target and distractors. In present study, two experiments were conducted to investigate the effect of motion direction and velocity on visual search on screen. In Experiment 1, participants were required to complete the search task at three velocities(2, 8, and 16 deg/s) and four directions of motion(up, down, left, right). In Experiment 2, participants finished the more difficult visual searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
3
3
0
Order By: Relevance
“…There was evidence that the increase in actual speed gives rise to apparent speed, which is consistent with the previous research [40,47]; it was also found that a cubic equation could be used to illustrate the quantitative relationship between actual speed and apparent speed. The study also discovered that higher speeds have a detrimental impact on the accuracy rate of response, which aligns with the previous research [23,48]. The emergence of this phenomenon can be attributed to the presence of motion blur effects, when movement speed exceeds 32 • /s, the degree of motion blur could be more serious [23,32], which made it more difficult for observers to see the image clearly.…”
Section: Discussion Of Experiments IIsupporting
confidence: 88%
See 4 more Smart Citations
“…There was evidence that the increase in actual speed gives rise to apparent speed, which is consistent with the previous research [40,47]; it was also found that a cubic equation could be used to illustrate the quantitative relationship between actual speed and apparent speed. The study also discovered that higher speeds have a detrimental impact on the accuracy rate of response, which aligns with the previous research [23,48]. The emergence of this phenomenon can be attributed to the presence of motion blur effects, when movement speed exceeds 32 • /s, the degree of motion blur could be more serious [23,32], which made it more difficult for observers to see the image clearly.…”
Section: Discussion Of Experiments IIsupporting
confidence: 88%
“…The study also discovered that higher speeds have a detrimental impact on the accuracy rate of response, which aligns with the previous research [23,48]. The emergence of this phenomenon can be attributed to the presence of motion blur effects, when movement speed exceeds 32 • /s, the degree of motion blur could be more serious [23,32], which made it more difficult for observers to see the image clearly. Additionally, some evidence indicates that observers experienced more visual fatigue symptoms as the speed increased, including eye fatigue, dryness, and discomfort.…”
Section: Discussion Of Experiments IIsupporting
confidence: 88%
See 3 more Smart Citations